Collagen concentration and biomechanical properties of samples from the lower uterine cervix in relation to age and parity in non-pregnant women - Bor Pinar; Danielsen Carl; Brüel Annemarie; Ørtoft Gitte; Oxlund Birgitte S; Oxlund Hans; Uldbjerg Niels (BMC, 2010)
Abstract Background During normal pregnancy the cervix has a load bearing function. The cervical tissue consists mainly of an extracellular matrix (ECM) rich in collagen; important for the biomechanical properties. The aim of the present study was to evaluate how the biomechanical strength of samples from the distal cervix is associated with collagen content in relation to age and parity. This study demonstrates a method to investigate cervical tissue from women who still have their uterus in situ. Methods Cervical punch biopsies (2 × 15 mm) were obtained from 57 healthy women (median age: 39 years, range: 29-49 years). Biomechanical tensile testing was performed, and collagen concentration (as % of dry defatted weight (DDW)) and content (mg of collagen per mm of specimen length) was determined. Histomorphometry was used to determine the volume densities of extracellular matrix and smooth muscle cells. Smooth muscle cells were identified by immunohistochemistry. Finally, orientation of collagen fibers was estimated. Data are given as mean +/- SD. Results The mean collagen concentration (62.2 +/- 6.6%) increased with age (0.5% per year, r = 0.45, p = 0.003) and decreased with parity (1.7% per birth, r = -0.45, p = 0.033). Maximum load was positively correlated with collagen content (mg of collagen per mm of specimen length) (r = 0.76, p < 0.001). Normalized maximum stiffness was increased with age (r = 0.32, p = 0.017), whereas no correlation was found with regard to parity. In tissue samples with a length of approximately one cm, volume density of smooth muscle cells increased gradually from 8.9% in the distal part near the epithelium, to 15.5% in the proximal part (p < 0.001). Conclusions The present study shows that cervical collagen concentration increases with age and decreases with parity in non-pregnant women. In addition, collagen stiffness increased with age, whereas no change in collagen tensile strength with respect to age and parity was found. These results show that collagen contributes to cervical tissue tensile strength and age and parity should be considered confounding factors.